Editorial: Dossier Language teaching and everyday practices: dialogic-decolonial perspectives in pedagogical work with text - Moreira, Tatiana Aparecida; Costa, Ilioni Augusta da (The ESPecialist, 2025)
Several issues are debated in the school environment, in the different curricular components and in the various educational segments. Freire’s principles of Pedagogy of Autonomy invite us to undertake a process of reflection on our own teaching practice, since they show us that teaching requires thinking critically about our own practice and that teaching requires the conviction that change is possible, in addition to being aware of the incompleteness that is inherent to human beings. In classroom relationships, this incompleteness is plural, since “we are only because we are being” (Freire, 2002, p. 16).